T3 THYROTOXICOSIS AS A PARANEOPLASTIC MANIFESTATION OF METASTATIC EXTRAGONADAL NONSEMINOMATOUS GERM CELL TUMOUR - Diah, Mohd Idris Mohamad; Ooi, Xin-Yi; Wong, Hui Chin; Nagaratnam, Shamharini; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Nonseminomatous germ cell tumours (NSGCTs) are rare malignancies that arise from gonadal or extragonadal sites and comprise various histological subtypes. In 90% of cases, β-human chorionic gonadotropin (β-hCG) is elevated, with extreme levels occasionally inducing thyrotoxicosis via TSH receptor cross-reactivity. CASE We report a case of metastatic extragonadal NSGCT presenting with T3 thyrotoxicosis. A 22-year-old Malay male with no prior medical history developed progressive abdominal pain, nausea, vomiting and a 20 kg weight loss over four months. On arrival at the emergency department, he was hypertensive (153/120 mm Hg) and tachycardic (132 bpm). Examination revealed a 3 × 3 cm left cervical lymph node but no signs of hyperthyroidism. Initial thyroid function tests showed suppressed TSH (0.017 mU/L), normal free T4 (20.82 pmol/L), and elevated T3 (6.6 mU/L), consistent with T3 thyrotoxicosis. He was initiated on carbimazole 20 mg OD. TSH receptor antibody was negative. He required intensive care admission for heart failure, where echocardiography revealed global hypokinesia with a left ventricular thrombus. Further evaluation with a contrast-enhanced CT scan of the neck, thorax, abdomen and pelvis showed extensive cervical, mediastinal and abdominal lymphadenopathy, as well as a large lobulated left suprarenal mass (6.7 × 6.5 × 6.4 cm) with necrosis. Workup for adrenal hyperfunction was negative, and a markedly elevated β-hCG (250,573.0 U/L) led to a revised diagnosis of metastatic extragonadal NSGCT with paraneoplastic thyrotoxicosis. A cervical lymph node biopsy confirmed the diagnosis. Antithyroid therapy was tapered to achieve normal T3 levels. He was then referred for chemotherapy. His thyroid function normalised following treatment and carbimazole was discontinued, coinciding with a decline in β-hCG levels. CONCLUSION This case highlights the importance of considering paraneoplastic thyrotoxicosis in patients with unexplained hyperthyroidism and systemic symptoms, particularly in the context of extreme β-hCG elevations. Early recognition and appropriate oncological management are crucial for optimising outcomes.